Fasting glycemia in sleep disordered breathing: lowering the threshold on oxyhemoglobin desaturation. - Stamatakis, Katherine; Sanders, Mark H; Caffo, Brian; Resnick, Helaine E; Gottlieb, Dan J; Mehra, Reena; Punjabi, Naresh M (Sleep, 2008)
STUDY OBJECTIVES: Commonly used definitions of sleep-disordered breathing (SDB) are based on identifying discrete events of breathing abnormalities during sleep that are accompanied by an oxyhemoglobin desaturation (delta SaO2) of at least 4%. However, it is not known whether disordered breathing events with oxyhemoglobin desaturation less than 4% are associated with clinical sequelae such as abnormalities in fasting glycemia. DESIGN: Cross-sectional study. SUBJECTS AND SETTING: Participants from the Sleep Heart Health Study (SHHS) with a fasting glucose measurement made within a year of the baseline polysomnogram. MEASUREMENTS AND RESULTS: SDB severity was defined using the apnea-hypopnea index (AHI) and the hypopnea index (HI) by counting events with different levels of oxyhemoglobin desaturation (0.0%-1.9%, 2.0%-2.9%, 3.0%-3.9%, > or = 4.0%). Fasting glucose levels were used to classify individuals into normal (<100 mg/dL), impaired (100-125 mg/dL), and diabetic (> or = 126 mg/dL) groups. Ordinal logistic regression was used to determine the adjusted relative odds of an abnormal glucose value across quartiles of the hypopnea index, independent of factors such as age, body mass index, waist circumference, and usual sleep duration. The prevalence of impaired and diabetic fasting glucose in the analytical sample was 32.9% and 5.8%, respectively. The covariate-adjusted relative odds of impaired or diabetic fasting glucose in the highest versus the lowest AHI quartile was 1.35 (95% CI: 1.04-1.76) for events with a delta SaO2 > or = 4.0%, 1.72 (95% CI: 1.20-2.48) for events with a delta SaO2 between 3.0%-3.9%, 1.41 (95% CI: 1.07-1.86) for events with a delta SaO2 between 2.0%-2.9%, and 1.07 (95% CI: 0.84-1.37) for events with a delta SaO2 between 0.0%-1.9%. The corresponding odds ratios for the HI were 1.47 (95% CI: 1.13-1.92), 2.25 (95% CI: 1.59-3.19), 1.44 (95% CI: 1.09-1.90), and 1.15 (95% CI: 0.90-1.47), respectively. CONCLUSIONS: The results of this study indicate that SDB events accompanied by oxyhemoglobin desaturation of between 2% to 4% are associated with fasting hyperglycemia. These findings suggest that milder degrees of SDB may predispose to adverse metabolic outcomes.
Keywords: Aged; Blood Glucose; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Male; Middle Aged; Odds Ratio; Oxygen; Oxyhemoglobins; Polysomnography; Reference Values; Sleep Apnea, Obstructive